Pharmaceutical evaluation and dynamic vapor sorption studies of fast dissolving intraoral films of Loratadine. (December 2013) - Arya, Arun; Sharma, Vijay; Pathak, Kamla
Abstract : The aim of the study was to develop intraoral films (IOFs) of loratadine and to assess the storage conditions by dynamic vapour sorption studies. The excipient selection was guided by drug excipient compatibility studies and the incompatibility of loratadine with dibutylphathalate and Tween20 was confirmed by Electro-spray Ionization Mass Spectrometry. Thus intaroral films were developed using HPMC E-15 LV and polyvinyl alcohol (PVA) as lone and mixed film formers to get eighteen formulations (F1- F18) that varied in the type and amount of plasticizer used. Four formulations selected on the basis of pharmacotechnical characteristics were improvised by inclusion of Poloxamer407 that lowered the dissolving time to the tune of 36–55%. Dynamic vapour sorption studies of the improvised films (PF1-PF4) demonstrated an increase of 2% by weight at 50% relative humidity (RH) and 25°C suggesting storage of the films below the stated conditions. In vitro drug release studies in phosphate buffer pH 6.8 demonstrated more than 94% cumulative drug release from the formulations. Analysis of model independent parameters identified PF2 as the best formulation that was nine times superior in its dissolution efficiency to Lorafast tablets ® .